Conflict and peasant protest in the history of a Macedonian village: 1900-1935 - Vermeulen, Hans (The Greek Review of Social Research, 1981)
In thestudy of the role peasants have played in the political life of the country too little attention has been payed to regional variation and its explanation. During the first part of this century peasants in the Eastern Macedonia participated more in opposition parties, such as Agrarian and the Communist Party than most peasants in Greece. This article tries to explore some of the factors which contributed to peasant protest in Eastern Macedonia, especially in one particular village. In the first decade of this century conflicts developed between the most powerful families in the village and a brotherhood in which mid dle peasants had much influence. The internal conflicts, which were related to developments at other levels, increased during the follow ing decades and look on a more ideological character when the Agrarian and Communist Parties established themselves in the village. The takeover by Metaxas found part of the village population in a revolutionary atmosphere. A number of factors have been considered in order to explain the political developments during the pre-Metaxas period. Oneof these is the expansion of tobacco cultivation which made the peasants less dependent on local powerholders, brought them intocontact with ur ban laborers and made them more dependent on international markets. Others include the late incorporation into the Greek state and the relatively closed character of the village community which help to explain why the village was not drawn into the dominant political discourse on the issue of the monarchy.